Exploring the impact and cultural differences in debate methodology for education and youth work - Bojan Marjanovic (22590572) (2025)
This conference contribution was presented by Bojan Marjanovic, Nikola Baketa, Marko Kovacic, Mirta Mornar, International Debate Education Association. (Qatar International Conference on Debate and Dialogue. An Initiative of QatarDebate 2025). We examine the impact of debate methodology on youth education, formal and non-formal, highlighting its historical and cross-cultural dimensions. Quantitative and qualitative data from students and debate educators is used to assess skill development in argumentation, oracy, and civic engagement. Results emphasize that active methods such as structured exercises and practice debates significantly enhance critical thinking, political literacy, and community involvement compared to traditional lectures. Qualitative insights further illustrate how debate participation shapes students' interpersonal skills and civic awareness. We suggest broader research, especially longitudinal and cross-cultural studies, to improve understanding of debate’s effectiveness across diverse educational contexts and methodologies. Other Information Conference information: The 2nd International Conference on Debate & Dialogue : An Initiative of QatarDebate (19 - 20 May 2025, Qatar National Conventions Center - QNCC, Doha - Qatar) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://qatardebate.org/programs/academic-programs/2nd-icdd/